2020
DOI: 10.1016/j.jdiacomp.2020.107748
|View full text |Cite
|
Sign up to set email alerts
|

The early impact of the COVID-19 pandemic on adults with type 1 or type 2 diabetes: A national cohort study

Abstract: Aims To describe the effects of the COVID-19 pandemic on adults with T1D or T2D in the U.S. Methods Participants, recruited from the Taking Control of Your Diabetes Research Registry, were ≥19 years old and diagnosed with either T1D or T2D for ≥12 months. Participants completed an online survey on a HIPAA-protected platform. Results Completed surveys were received from 763 T1Ds and 619 T2Ds. Average T1D age was 53.3 (SD = 15.3); average T2D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
3
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 16 publications
8
115
3
9
Order By: Relevance
“…Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 . In a study from France, 45% of 195 patients with chronic heart disease had a >25% reduction in physical activity and 24% of patients had gained >2kg weight 229 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 . In a study from France, 45% of 195 patients with chronic heart disease had a >25% reduction in physical activity and 24% of patients had gained >2kg weight 229 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] For example, a study in individuals diagnosed with T2DM and followed in a tertiary care centre in India, showed that only 24% met a physician during the lockdown (23 March to 23 June 2020), and that the vast majority of patients undergoing blood glucose monitoring (81%) had insufficient glycaemic control. 17 The deleterious impact of the ongoing pandemic on T2DM management probably involves the overload of healthcare systems 12,21 and delays in seeking medical care because of fear of contracting COVID-19. 22 Although previous studies have allowed a better understanding of the effects of the COVID-19 pandemic on the care of people with diabetes, they have at least two major limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Data on telemedicine and type 2 diabetes in the COVID-19 era are still lacking. In a recently published study including 763 type 1 and 619 type 2 diabetics, about 40% of patients stated that all of their diabetes visits were cancelled or postponed, 40% were switched to telehealth consultations, while half reported lower overall satisfaction with these visits[ 16 ].…”
Section: Introductionmentioning
confidence: 99%